The prevalence of pseudoexfoliation syndrome and possible systemic associations in patients scheduled for cataract surgery at the Military Medical Academy in Belgrade - Kovač, Bojan; Vukosavljević, Miroslav; Petrović Janićijević, Mirjana; Resan, Mirko; Janković, Janko (Vojnosanitetski pregled, 2014)
Background/Aim. Pseudoexfoliation syndrome (PEX) is an age-related systemic degenerative disorder characterized by the production and progressive accumulation of extracellular fibrillar eosinophilic material in the anterior segment of the eye. The aim of the study was to evaluate several clinical aspects of PEX, such as frequency of PEX and pseudoexfoliation glaucoma (PEXG), intraocular pressure (IOP), the type of lens opacity, and the possible relationship of PEX and systemic diseases. Methods. All 674 cataract patients had a comprehensive eye examination, including slitlamp biomicroscopy before and after mydriasis, IOP measurement, and fundus examination. The patients were classified into two groups: the PEX and the non-PEX group. Results. The overall prevalence of PEX syndrome was found to be 17.5% (118 patients). The mean age of PEX patients (79.7 ± 6.1 years) was significantly higher when compared with those without PEX (73.5 ± 9.1 years) (p = 0.000). The prevalence of PEX syndrome was found to increase with age, from 7.3% in the 7th decade of life to 27% in patients older than 80 years (p < 0.001). The most common cataract type in the PEX patients was mature cataract observed in 40.7% of patients. The rest of the patients had mixed (30.5%), nuclear (25.4%), cortical (1.7%) and hypermature cataract (1.7%). Among the PEX patients 44 (37.2%) had glaucoma. Intraocular pressure was significantly higher in eyes with pseudoexfoliations than in eyes without it (17.8 ± 3.2 mmHg and 15.8 ± 2.8 mmHg, respectively; p = 0.001). Moreover, the prevalence of coronary heart disease was found to be higher in PEX patients. Conclusion. PEX syndrome is a common problem among Serbian patients scheduled for cataract surgery. It represents one of the major glaucoma risk factors and probably associated with ischemic heart disease, intraoperative and postoperative problems in cataract surgery.
Keywords: exfoliation syndrome; cataract; glaucoma; prevalence; coronary artery disease; intraoperative complications; postoperative complications